Relación entre satisfacción laboral y síndrome de burnout en docentes de colegios - Villanueva Laos, Ana Teresa Leonilda (2021)
In the last 20 years, about 30% of teacher suffer from burnout; being the working conditions being the working conditions, the overload of students in the classroom, coordinating with their classmates curriculum issues, and taking work home the causes of this. This leads to the emotional condition of the teachers being affected, affecting the teaching – learning process and its quality, since the interaction with the student becomes distant. The variables to be analyzed are job satisfaction and burnout syndrome; therefore, the objective of this work is to study the relationship between burnout and job satisfaction in public and private school teachers who teach at the primary and secondary level, by means of a systematic review of eight articles, which were selected through the PRISMA guidelines and the databases consulted were Scielo, Proquest and Scopus. It is found that there is a negative correlation between both variables. In the findings, job satisfaction will be affected according to the subject they teach due to the demand of parents; as well as public school teachers show a lower level of job satisfaction, which is why they are more likely to suffer from burnout. Likewise, there is significance. Likewise, there is significance between the amount of work experience and job satisfaction and burnout. On the other hand, no relationship was found between the variables and age. In conclusion, it has been found that the job satisfaction variable predicts burnout and is also a protective variable, hence its negative correlation.